[Nurse interventions and the complications in the post-anesthesia recovery room]. - Débora Cristina Silva Popov; Aparecida de Cássia Giani Peniche (2009)
The objective of this study was to identify the prevalent complications in the postanesthesia recovery room (PARR), and correlate nurses' work hours with the complications. The sample consisted of 400 records of patients older than 18 years, who had major and medium surgical procedures, admitted at the PARR unit, with a stay of at least one hour. The prevalent complications were pain and hypothermia. The following complications showed a statistically significant relationship with the nursing intervention: pain: routine, oxygen therapy, medication and bandages; agitation/anxiety: routine and oxygen therapy; hypotension: hydration, complementary exams, and observation; hypertension: observation; tremor: mat heater, blood transfusion; nausea/vomiting: routine, medication and urinary catheterization; bleeding: routine, medication and bandages; hypoxemia: routine and oxygen therapy; hypothermia: routine, mat heater, and medication. Pain, nausea/vomiting, agitation and bleeding showed a statistically significant relationship with the PARR nurse.